2017
DOI: 10.5792/ksrr.16.035
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Clinical Outcomes of Revision Total Knee Arthroplasty

Abstract: PurposeThe purpose of this study was to evaluate causes and clinical outcomes of revision total knee arthroplasty (TKA) with a minimum 2-year follow-up.Materials and MethodsWe performed a retrospective review on the records of 225 revision TKAs performed from 2003 to 2012 at a single institution. Finally, 206 cases were conducted. To evaluate clinical outcomes, we checked the range of motion (ROM), Knee Society (KS) score, Hospital for Special Surgery (HSS) score, and Western Ontario and McMaster Universities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 21 publications
5
45
1
Order By: Relevance
“…MCID is an important concept used to determine whether a medical intervention improves perceived outcomes in patients. 17 While previous studies on rTKA did demonstrate significant improvements in outcomes, 14,15 to the authors' knowledge this is the first to analyze the results using the MCID criteria.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…MCID is an important concept used to determine whether a medical intervention improves perceived outcomes in patients. 17 While previous studies on rTKA did demonstrate significant improvements in outcomes, 14,15 to the authors' knowledge this is the first to analyze the results using the MCID criteria.…”
Section: Discussionmentioning
confidence: 96%
“…Five-year outcomes of revision TKA stratified by cause Kim et al, in their study of 228 knees, reported a mean flexion of 105 degrees, KSKS of 87.9, and a KSFS of 64. 14 In a recent study by Lee et al, 225 patients who underwent rTKA achieved a mean KSS of 82.6 at a minimum follow-up of 2 years 15. However, the SF-36 outcomes for this study's cohort of patients are a cause for concern.…”
mentioning
confidence: 80%
“…This was a retrospective study that started with 154 patients, who underwent primary TKA using the same prosthesis due to end-stage osteoarthritis (OA) at our institution, from February 2014 to November 2015. Of these, 16 were excluded because of a history or objective evidence of rheumatoid arthritis [5], posttraumatic arthritis [6], concomitant neuronal disease [3], weakness or severe instability in the operated limb [2]. Patients who with less than 2 years of follow-up were also excluded [8].…”
Section: Methodsmentioning
confidence: 99%
“…Proper implant positioning and sizing are crucial for successful total knee arthroplasty (TKA) [1][2][3][4]. Anterior referencing (AR) and posterior referencing (PR) systems are the two major systems for positioning and sizing of the femoral component.…”
Section: Introductionmentioning
confidence: 99%
“…Most rTKA failures occur in the first two years following surgery [ 23 ]. Infection, aseptic loosening, and instability are categorized as the three main causes for failure following rTKA surgery [ 24 , 25 , 26 , 27 ]. Although infection is the principal cause of complication after rTKA, periprosthetic fracture, extensor mechanism insufficiency and stiffness increase the risk of further surgical intervention [ 28 ].…”
Section: Complications After Rtkamentioning
confidence: 99%